Moral disengagement and unethical decision making: Systematic literature review - Sulistyowati, Sulistyowati (Indonesian Journal of Business, Accounting and Management, 2025)
The development of technology and a complex business environment poses an increased risk of unethical behavior among individuals and organizations. The concept of moral disengagement, introduced by Bandura (1999), has become a framework for understanding the psychological mechanisms that enable individuals to relinquish their moral standards and engage in unethical actions without feeling guilty. Research: This study investigates the relationship between moral disengagement and decision-making without ethical review by systematically reviewing empirical and theoretical studies on planned behavior theory. Analysis results indicate that a high level of moral disengagement increases the likelihood of unethical behavior, which can lead to negative consequences for organizations, including damage to reputation and a decline in stakeholder trust. Therefore, understanding and preventing moral disengagement is very important. To create an ethical and responsible organization​, answer. Research confirms the need for a development strategy that is culture-based, organization-based, and grounded in moral values and integrity, to support ethical behavior at all levels of the organization.